Numerical simulation on morphological process for Thuan An coastal area - Chung, Dang Huu (Vietnam Journal of Mechanics, 2001)
The 2DH model is developed and applied to evaluate sediment transport and bed level change in the coastal zone in central Vietnam. The model took the influences of waves and wind into account. Three different options for the flows with or without wind and two wave regimes are calculated. The computed results for flows are calibrated on the base of data measured in Thuan An station in April 1999. The final results from sediment transport model showed that the near shore area from Thuan An to Tu Hien are strongly affected by sediment transport process and the natural flow could change the morphological bed for very long time.